2019
DOI: 10.1111/1755-0998.13034
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐level genome of black rockfish, Sebastes schlegelii, provides insights into the evolution of live birth

Abstract: The black rockfish (Sebastes schlegelii) is a teleost in which eggs are fertilized internally and retained in the maternal reproductive system, where they undergo development until live birth (viviparity). In the present study, we report a chromosome‐level black rockfish genome assembly. High‐throughput transcriptome analysis (RNA‐seq and ATAC‐seq) coupled with in situ hybridization (ISH) and immunofluorescence reveal several candidate genes for maternal preparation, sperm storage and release, and hatching. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 69 publications
0
49
0
Order By: Relevance
“…We previously reported that the NO-sGc-cGMP signaling pathway was identi ed in WGCNA co-expression module of ovarian wall, and proposed that the rock sh ovarian wall has a similar function to the uterus of mammals [4]. The chemical messenger NO is an endothelium derived relaxing factor, which participates in the control of vasorelaxation in fetoplacental vessels [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the NO-sGc-cGMP signaling pathway was identi ed in WGCNA co-expression module of ovarian wall, and proposed that the rock sh ovarian wall has a similar function to the uterus of mammals [4]. The chemical messenger NO is an endothelium derived relaxing factor, which participates in the control of vasorelaxation in fetoplacental vessels [47].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we revealed the adaptation of black rock sh to viviparity based on both the genomic and transcriptomic evidences. We found genes related to placental development, cell adhesion, trophoblast invasion, calcium-sensing receptors, the NO-sGc-cGMP signalling pathway, and blood vessel function were co-expressed in the ovarian wall [4]. We thus hypothesized that the ovarian wall of black rock sh had the function similar to the mammalian uterus.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Embryos at six different stages (1-cell, 32-cell, blastula, gastrula, somite and pre-hatching) were collected as described in our previous study [12]. Then, they were stored at -80℃ for further use.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The black rockfish (S.schlegelii, hereafter denoted 'rockfish') evolving live birth, is a good model of teleost to study the adaption to viviparity [12]. Some studies have been carried out focusing on the genes related to development, growth, immunity, and reproduction in this group of fish [13][14][15].…”
Section: Introductionmentioning
confidence: 99%